2015
DOI: 10.5552/drind.2015.1403
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Thermal Properties of Cellulose Nanofibrils Reinforced Epoxy Nanocomposites

Abstract: • Epoxy resins have gained attention as important adhesives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…It is mainly influenced by chain mobility, intermolecular reaction, branching, and crosslinking degree . In most studies, the T g of nanocomposites exhibits no significant changes with the addition of nanocellulose, with examples including epoxy and gluten composites . Furthermore, Niazi et al .…”
Section: Thermal Properties Of Nanocellulose Compositesmentioning
confidence: 99%
“…It is mainly influenced by chain mobility, intermolecular reaction, branching, and crosslinking degree . In most studies, the T g of nanocomposites exhibits no significant changes with the addition of nanocellulose, with examples including epoxy and gluten composites . Furthermore, Niazi et al .…”
Section: Thermal Properties Of Nanocellulose Compositesmentioning
confidence: 99%
“…The X c values calculated using XRD patterns were 33.5% for neat PLA nanofibrils. Also, poor dispersion and aggregation of CNF in the biopolymer matrix was found as presented by Yusra et al, 60 Aydemir, 61 and Chai et al 62 This status might be indicated the degradation in the matrix due to chain scission/cleavage occurred in the highly crystallized PHB regions. 63,64 However, it was not detected any crack or slits on the BNCs expect for the PHB50-PLA50-CNF0.5, but it was detected to be the white spots on the surface of the all blends and the BNCs due to raised surface roughness, and photo-oxidation as a result of degradation reactions 65 as shown in Figure 9B-E,H.…”
Section: Rheology Characterizationmentioning
confidence: 92%
“…For example, Omrani et al [132] reported that direct dispersion of CNFs in epoxy resin could cause agglomeration of CNFs when the content reached 0.5 phr. It is generally believed that the content of cellulose is the key factor to affect the dispersion, and the high content of nanocellulose is difficult to disperse in epoxy with high viscosity [133]. Emami et al [103] found that the optimal content of CNCs reinforcing epoxy resin is about 2%.…”
Section: Dispersion Strengthening Strategymentioning
confidence: 99%